Advancements in Hybrid Photovoltaic-thermal Systems: Performance Evaluations and Applications. (November 2016) - Noro, Marco; Lazzarin, Renato; Bagarella, Giacomo
Abstract: Due to European Directives the electric and thermal energy needs of new and retrofitted buildings have to be satisfied by increasing percentages of renewable energy. Solar energy and heat pumps are the most promising technologies mainly in residential buildings as they have reached great maturity. PhotoVoltaic / Thermal cogeneration (PV/T) aims to utilize the same area both for producing electricity and heat. As solar cells are sensitive to temperature (their efficiency lowers when temperature increases), heat is beneficially collected. This paper provides a description of the applications of the photovoltaic–thermal systems, such as building integrated PV/T, concentrating PV/T systems and photovoltaic–thermal heat pump systems.